Copyright and Innovative Technologies - Sadler, Pauline; Sadler, Peter (School of Business Law, Curtin Business School, Curtin University of Technology, 2008)
This article examines how the Australian legal system manages copyright issues related to the development of innovative technologies, focusing in particular on how the Copyright Act 1968 (Cth) (CA) enforces the effect of ‘technological protection measures’ and ‘access control protection measures’ by proscribing the use of ‘circumvention devices’. Cases referred to are Autodesk v Dyason [1992] HCA 2 and Stevens v Kabushiki Kaisha Sony Computer Entertainment & Ors [2005] HCA 58. Legislation discussed is the Copyright Act 1968 (Cth), Copyright Amendment (Digital Agenda) Act 2000 (Cth), Copyright Amendment Act 2006 (Cth). Reference is also made to the Australia-United States Free Trade Agreement.